Loss aversion and perceptional risk aversion - Mario Alessandro Maggi (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2004)
This paper analyzes, for S-shaped value functions, the relations between loss aversion and perceptional risk aversion (i.e. computed with the perceived probability weights) in Cumulative Prospect Theory. We show that perceptional risk aversion for mixed sign lotteries is equivalent to weak loss aversion, so this is the right assumption to get a sensible behavior towards risk. No assumption on the probability distortion is needed, beside the basic ones. Next we show a case (the widely used power S-shaped value function) where the lack of loss aversion can lead to a puzzling behavior with respect to risk.
Keywords: D81; 330; Cumulative Prospect Theory; power S-shaped value function; reference dependence utility; loss aversion; Entscheidungstheorie; Risikoaversion; Glücksspiel; Theorie